Hubungan antara Kepercayaan, Sikap terhadap Pengobatan Suntik dengan Intensi Meminta Suntik di Kabupaten Gunungkidul - Muchamad Agus Priyanto, Sumarni D.W., Fatwa Sari Tetra Dewi (Berita Kedokteran Masyarakat (BKM), 2003)
Background: The use of injection treatment in Gunungkidul regency is relatively high and has increased continually. Previous research showed that the high use of injection was occurred because of patient's request. This research was aimed to investigate the relationship and influence between: normative belief, attitude toward injection treatment, belief toward injection request, attitude toward patient request and intention of injection request.Methods: This research was using cross-sectional design with quantitative and qualitative approaches. Using multistage sampling chose the sample. The population was the inhabitant of Gunungkidul regency. Qualitative approach was used to collect issues to developed questionnaire. Quantitative data was analyzed by using multiple regressions.Results: The result of this research showed that most of the sample were certain that his or her social environment expected him or her to ask for injection in every treatment; part of the sample were also convinced that the injection request had a beneficial consequence. However, most of the sample did not support the superiority of injection treatment, likewise attitude toward injection request and intention toward injection request.Conclusions: It can be concluded that attitude toward injection request and normative belief could give great influence toward injection request. Indeed, normative belief is the most important direct or indirect intention determinant to ask for injection. Keywords: injection,belief,attitude,intention